The Tea Tree Consecration Ceremony of Bulang Tradition under the Theravāda Buddhism in Laoman’e Village: An Empirical Study - Yan, Wenen (Journal of International Buddhist Studies, 2023)
This study focuses on the tea tree consecration ceremony of the Bulang ethnic people in the Laoman’e village of Xishuangbanna (Yunnan) China. The study applied the qualitative research method in the sociological approach to religious studies. This consists of an in-depth interview with 17 research subjects, and the samples were selected from the Bulang ethnic community who are knowledgeable about the tea culture and religion in the Laoman’e village of Xishuangbanna, Yunnan. There are a total of three objectives in this research study: 1) to study the historical background of tea and how tea culture influences Theravāda Buddhism in Yunnan, 2) to investigate tea culture in relation to Theravāda Buddhism, and 3) to analyze the importance of the tea tree consecration ceremony in Bulang society. The first finding strongly indicates a long-standing relationship between tea-drinking culture and Buddhism, since both were brought to China from the nearby country of India. The second finding suggests that there are two methods used to perform the tea tree consecration ceremony: traditional rituals and Theravāda Buddhist culture. And the third finding shows that the Bulang ethnic group places great significance on the tea tree consecration ceremony and its culture in terms of economics, Buddhism, culture, rites and rituals, and society at large.